2013
DOI: 10.1111/cga.12006
|View full text |Cite
|
Sign up to set email alerts
|

Bifid choroid plexus: Always a normal fetal brain structure variant?

Abstract: Choroid plexus, a fetal organ developing approximately from the sixth week of gestation, plays a fundamental role in developing fetal brain organization. As relatively little is known about the relationship between anomalies of choroid plexuses structure and their role in brain function, we examined cases of bifid choroid plexus (BCP) and discussed their potential association with lateral ventriculomegaly, other abnormal ultrasound findings, and their potential role as markers of fetal chromosomal abnormalitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 21 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…Abnormal CP has been recently described by Centini et al. () in 23 out of 2145 routine second trimester scans (an incidence of 1.07%). Centini et al.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Abnormal CP has been recently described by Centini et al. () in 23 out of 2145 routine second trimester scans (an incidence of 1.07%). Centini et al.…”
Section: Discussionmentioning
confidence: 87%
“…In the case reported by Angle et al (1998) a C-to-A change at nucleotide 1620 (C1620A) in the tyrosine kinase domain of the FGFR3 gene was demonstrated, thus providing supportive evidence that a mutation in the FGFR3 gene may result in altered growth in both cranial and long bones. Abnormal CP has been recently described by Centini et al (2013) in 23 out of 2145 routine second trimester scans (an incidence of 1.07%). Centini et al (2013) concluded that dysmorphic CP may be a variant of normalcy and may be seen also associated with multiple congenital anomalies such as corpus callosum abnormalities, ventriculomegaly, incarcerated lumbar hemivertebra and, trisomy 9.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations